(untitled) (Revista Ciência Agronômica, 2020)
The use of a cropping system that provides producers with better land use, higher productivity per unit area, greater diversification in production, and, consequently, agro-economic advantages, is the choice of many vegetable producers. To meet the demands of these producers, experiments were conducted under field conditions in a semi-arid environment to evaluate the production and agro-economic benefits of carrot x vegetable cowpea associations as a function of green manuring with biomass of Merremia aegyptia L., a spontaneous species from the Caatinga biome, in different spatial arrangements at two cropping years. The experimental design was a randomized complete block design with treatments arranged in a 4 x 3 factorial scheme, with four replications. The first studied factor was the amounts of M. aegyptia biomass (20, 35, 50, and 65 t ha-1 on a dry basis), while the second factor was the spatial planting arrangements (2:2, 3:3, and 4:4), corresponding to rows of carrot alternated with rows of vegetable cowpea. The production optimization of the carrot and cowpea cultures was achieved with the incorporation of the M. aegyptia biomass amounts of 32.69 and 50.17 t ha-1, respectively, and agro-economic optimization of the entire intercropping system was obtained at a biomass amount of 34.66 t ha- ¹. The spatial planting arrangement of 2:2 resulted in the greatest agro-economic efficiency of the crop association.